“Moda boa”: música caipira e cotidiano (Fernandópolis/SP – 1955-1975) - Barroso, Bruno Godoi (2019)
The present study examines the dimensions of production and performance of the “caipira” musical genre in the city of Fernandópolis between the 1950s and 1970s, especially due to its relevance to the formation of identity ties and to the mobilization of varied emotions, both operated through the construction of rural and urban daily routines‟ practices and representations, which are described in the songs lyrics. The apprehension of this universe of bumpkin music production in the city of Fernandópolis occurs through the analysis of songs composed by city musicians, sometimes in partnership with colleagues from other municipalities from the region, as well as through testimonies of these composers, performers, and lovers of this musical genre. In this scenario, we highlight the role of Fernandópolis‟ radio station, “Rádio Cultura AM”, as a promoter of this culture, as a supporter for the formation of local and regional duets (through viola festivals), and as a disseminator of these duets music production, which ate the time were of national renown, connecting the listeners through entertainment and service provision. Those characteristics transformed, at the time, this station in the main means of communication between the countryside and the city in the Northwest of the state of São Paulo. Through these songs are depicted representations that capture the tensions between the countryside and the city in the midst of the soundscapes; the representativeness of the viola player as a chronicler of the bumpkin cultural scene; the masculine dimension of loves and passions; the nature as the materialization of the sacred. Important aspects that act in the configuration of Fernandópolis‟s bumpkin culture